High-resolution NMR of encapsulated proteins dissolved in low-viscosity fluids - Wand, A. Joshua (The National Academy of Sciences, 1998)
The majority of known proteins are too large to be comprehensively examined by solution NMR methods, primarily because they tumble too slowly in solution. Here we introduce an approach to making the NMR relaxation properties of large proteins amenable to modern solution NMR techniques. The encapsulation of a protein in a reverse micelle dissolved in a low-viscosity fluid allows it to tumble as fast as a much smaller protein. The approach is demonstrated and validated with the protein ubiquitin encapsulated in reverse micelles prepared in a variety of alkane solvents.